Case Report: A complicated case of neonatal refeeding syndrome following intrauterine growth restriction corrected by high dose thiamine supplementation - Wu, Yixiang; Xu, Hongxun; Du, Lizhong; Li, Zhongyue (Frontiers in Pediatrics, 2025)
Refeeding syndrome (RS), marked by severe electrolyte imbalances (e.g., hypophosphatemia, hypokalemia) and thiamine deficiency, poses significant risks during nutritional rehabilitation in intrauterine growth restriction (IUGR) neonates. This case report highlights the efficacy of high-dose thiamine (2 mg/kg IV) in resolving refractory RS in a preterm IUGR infant (34 weeks, 1,415 g) unresponsive to standard electrolyte correction. Despite gradual caloric reintroduction and parenteral supplementation, the infant exhibited persistent hypophosphatemia (3.0 mmol/kg/day IV requirement), hypokalemia (4.3 mmol/kg/day IV requirement), and thrombocytopenia (nadir 27 × 109/L). Thiamine administration led to rapid clinical improvement within 4 h, with electrolyte normalization (potassium: 2.19→4.41 mmol/L; phosphorus: 0.69 →2.35 mmol/L) and platelet recovery (27→112 × 109/L). The findings suggest thiamine deficiency may underlie refractory RS in IUGR neonates, advocating for early supplementation in high-risk cases. Further research is needed to optimize dosing and validate thiamine's role in RS management.